2016
DOI: 10.1155/2016/7342379
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tenogenic Differentiation Mediated by Extracellular Tendon Matrix and Short‐Term Cyclic Stretching

Abstract: Tendon and ligament pathologies are still a therapeutic challenge, due to the difficulty in restoring the complex extracellular matrix architecture and biomechanical strength. While progress is being made in cell-based therapies and tissue engineering approaches, comprehensive understanding of the fate of progenitor cells in tendon healing is still lacking. The aim of this study was to investigate the effect of decellularized tendon matrix and moderate cyclic stretching as natural stimuli which could potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 42 publications
4
60
2
Order By: Relevance
“…Injection within the mid‐substance of the scaffolds or the creation of small holes by needle puncture could also help for better distribution of cellular therapies within the matrix structure, but the impact of such techniques on the mechanical properties remains to be verified. Alternatively, mechanical stimulation by stretching of reseeded tendons could further induce tenogenic differentiation and cellular alignment that may improve tendon healing . Overall, both HE and MTT staining indicated that the F/T+NaCl 1M protocol was biocompatible and allowed sterile cell culture, proving promising for future clinical development.…”
Section: Discussionmentioning
confidence: 98%
“…Injection within the mid‐substance of the scaffolds or the creation of small holes by needle puncture could also help for better distribution of cellular therapies within the matrix structure, but the impact of such techniques on the mechanical properties remains to be verified. Alternatively, mechanical stimulation by stretching of reseeded tendons could further induce tenogenic differentiation and cellular alignment that may improve tendon healing . Overall, both HE and MTT staining indicated that the F/T+NaCl 1M protocol was biocompatible and allowed sterile cell culture, proving promising for future clinical development.…”
Section: Discussionmentioning
confidence: 98%
“…Increased collagen type I and tenomodulin expression; promoted cell elongation and alignment; and increased proliferation and ECM synthesis [238] Decellularized matrix GraftJacket showed the highest proliferation after 13 days in culture; Conexa exhibited the highest collagen type I and collagen type III expression; both had lower collagen type I to collagen type III ratio and exhibited no differences in tenogenic markers, compared to synthetic patches [209] 3D scaffold-free culture Filter well inserts led to cell aggregation and formation of macro-mass clusters capable of synthesizing more collagen types I, III, and V than monolayer cultures [165] Microgravity spheroid cultures upregulated collagens type I and III and scleraxis expression [167] High-density air-liquid cultures maintained decorin, COMP, and scleraxis expression and increased ECM synthesis, but formed tendon-like tissue with different gene profile to native tendon [150,151] TSPCs Aligned PLLA fibers Spindle-shaped morphology, aligned orientation, upregulated tenogenic markers, and downregulated RUNX-2 and ALP in osteogenic induction medium [154] Decellularized matrix Bone matrix promoted osteogenic differentiation, tendon matrix promoted tenogenic differentiation, dermal matrix had no effect [241] Decellularized tendon slices upregulated tenogenic markers [242] 3D scaffold-free culture High density cell sheets or spheroids maintained tenomodulin, Mohawk, and scleraxis expression [70] BMSCs Decellularized matrix Decellularized tendon slices upregulated tenogenic markers [243] Cells integrated and adopted tenogenic morphology when cultured on decellularized tendons [162] ADSCs Cells integrated and adopted tenogenic morphology when cultured on decellularized tendons [220] Decellularized equine tendons increased tenfold decorin expression [244] ESCs Electrospun fiber mats After 14 days in culture, 2 µm (as opposed to 0.5 and 1 µm) in diameter fibers increased collagen type I and scleraxis expression [175] Dermal fibroblasts 3D scaffold-free culture High density cultures upregulated decorin, tenomodulin, tenascin C, scleraxis, collagen type I, collagen type III, collagen type VI, TGF , BMP-12, and BMP-14 [85] can be easily manipulated to replicate native structural properties, synthetic materials alone cannot successfully maintain or direct phenotypes and are often shown to inhibit cellular attachment due to their hydrophobic surfaces. [155] As the main component of tendon, collagen is a popular material used to fabricate sponges, fibrous scaffolds, and hydrogels for tendon engineering applications.…”
Section: Cell Typementioning
confidence: 99%
“…Decellularized tendons subjected to 2% strain for 60 min, although upregulated tenogenic markers, there was no overall benefit of mechanical loading [244] in vitro culture environment is comprised of substantially dilute culture media that provide the minimal essentials for cell survival and growth. This is a stark contrast to the tissues from which the cells have been extracted, unsurprisingly leading to problems including phenotypic drift and suboptimal matrix production.…”
Section: Biochemical Biological Biophysicalmentioning
confidence: 99%
“…While excessive micromotion that may disrupt of the tissue healing interface between the labrum and the glenoid bone should be minimized during the early healing process, it should be also recognized that gradual application of controlled stress is likely a stimulus to cause further proliferation and differentiation of healing fibroblasts and may promote collagen fibers being laid down across the repair [18][19][20][21][22]. Hence, typical individuals are placed into an abduction brace for relative immobilization the first 6 weeks after surgery in order to protect the shoulder from positions that may place the repaired tissue at risk.…”
Section: Phase I: Immediate Phase After Anterior Labral Repair (0-6 Wmentioning
confidence: 99%
“…Phase III: Minimal Protection Phase After Anterior Labral Repair (12)(13)(14)(15)(16)(17)(18)(19)(20) Weeks)…”
Section: Phase I: Immediate Phase After Anterior Labral Repair (0-6 Wmentioning
confidence: 99%